ANALYTICAL STUDY ON DEVELOPMENT OF SECURITY FRAMEWORK FOR CLOUD COMPUTING - BHEEMASHANKAR, AMBALGI; A., C.SUBHAJINI (International Journal of Psychosocial Rehabilitation, 2020)
Cloud computing has changed the whole procedure that appropriated computing used to introduce, for example, lattice computing and server customer computing. Cloud computing portrays ongoing advancements in many existing IT technologies and isolates application and information assets from the basic foundation. Cloud computing security is a significant part of the nature of services from cloud service suppliers. Security concerns emerge when one starts to run applications past the assigned firewall and draw nearer towards the open space. Disregarding security in any part of the cloud can be a calamity for the association (the client) just as for the supplier. Right now, propose a cloud security model and security structure that distinguishes security challenges in cloud computing.